Learning in Country and Place - Heckenberg, Robyn (2020)
This paper focuses on the importance of connection to Country and the power of Story. It reflects on relationships to nature and the interconnectedness of place based learning and Traditional knowledge. Within these contexts, we look at Sovereignty and Belonging thematically: through Aboriginal art making and creative practice. As a Wiradjuri woman I have strong affiliations to River Country, so this is a river narrative which talks of curated community art projects and gallery showcasing to express place and love of Country.